The influence of the degree of activity of rheumatoid arthritis on the parameters of stable metabolites of nitric oxide - Sibirkina M.V. (Zien Journals, 2023)
Rheumatoid arthritis (RA) is an immunoinflammatory disease characterized by progressive destruction of joints and damage to internal organs, which is based on disturbances in the humoral and cellular immune system [1,2]. In the absence of effective therapy, life expectancy in patients with RA is lower by 3 years in women and 7 years in men, primarily due to the high risk of developing comorbid diseases [5].
Keywords: Rheumatoid arthritis; nitric oxide metabolites; red blood cells